17-z=13

Simple and best practice solution for 17-z=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-z=13 equation:


Simplifying
17 + -1z = 13

Solving
17 + -1z = 13

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + -1z = 13 + -17

Combine like terms: 17 + -17 = 0
0 + -1z = 13 + -17
-1z = 13 + -17

Combine like terms: 13 + -17 = -4
-1z = -4

Divide each side by '-1'.
z = 4

Simplifying
z = 4

See similar equations:

| 6p=208 | | 16t^2=223 | | 9[2-2x]=3x+2 | | 3y+20= | | (3x+10)=5x | | 15+7x-2x^2= | | 10x^3+12x^2+2x= | | 11x^2+x^3=0 | | 16t^2=338 | | 2x-45+1x+30=180 | | 2x^2+7x+15= | | 8n-7(n-8)=32+5n | | -10n+151=-589 | | 5b+14=-2(2-4b) | | (4h-2)=2(h+3) | | 8(v-8)=-8v-16 | | 44x-29=37x-15 | | 1-5x+3x+4=-3(x+8)+2(6x-2) | | 3+6n-7n=0 | | 2n+6=-20 | | 8s-[8+6s]=20 | | 2y+2y-3+3-7=42 | | 9(d+640)=522 | | (2-1)m=-3 | | 2-7(3v+7)=-131 | | 2x-2+6x=2(x+8) | | -2(x+5)=5x+39 | | 2a^2=20a-32 | | r/31--626=641 | | 4x^3-4x^2-9x-9=0 | | ln(3x+7)=50 | | 4(5x-3)=104-9x |

Equations solver categories